Comparative study of antioxidant activity and validated RP-HPTLC analysis of rutin in the leaves of different Acacia species grown in Saudi Arabia - Perwez Alam; Mohamed F. Alajmi; Ahmed H. Arbab; Mohammad K. Parvez; Nasir A. Siddiqui; Saleh I. Alqasoumi; Adnan J. Al-Rehaily; Mohammed S. Al-Dosari; Omer A. Basudan (Elsevier, 2017)
The present study assessed the comparative antioxidant potential of the ethanol extract (EE) of leaves of four Acacia species (Acacia salicina, AS; Acacia laeta, AL; Acacia hamulosa AH; and Acacia tortilis, AT) grown in Saudi Arabia, including RP-HPTLC quantification of antioxidant biomarker rutin. In vitro DPPH radical scavenging and β-carotene-linoleic acid bleaching assays showed the promising antioxidant activities of Acacia extracts: ASEE (IC50: 60.39 and 324.65 μg/ml) >ALEE (IC50: 217.06 and 423.36 μg/ml) >ATEE (IC50: 250.13 and 747.50 μg/ml) >AHEE (IC50: 255.83 and 417.28 μg/ml). This was comparable to rutin tested at 500 μg/ml. Further, a RP- HPTLC densitometric method was developed (acetonitrile:water; 6:4; v/v) using glass-backed RP-18 silica gel F254 plate, and scanned at UV max 254 nm. The method was validated as per the ICH guidelines. Analysis of the validated RP-HPTLC displayed an intense peak (Rf = 0.65 ± 0.004) of rutin that was estimated (μg/mg dry weight) to be highest in ASEE (10.42), followed by ALEE (2.67), AHEE (1.36) and ATEE (0.31). Taken together, presence of rutin strongly supported the high antioxidant property of the tested Acacia species, especially Acacia salicina. The developed RP-HPTLC method therefore, affirms its application in the quality control of commercialized herbal drugs or formulation containing rutin.